2019
DOI: 10.1523/jneurosci.2124-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries in Global Perception Are Represented in Near- versus Far-Preferring Clusters in Human Visual Cortex

Abstract: Human perception is more "global" when stimuli are viewed within the lower (rather than the upper) visual field. This phenomenon is typically considered as a 2-D phenomenon, likely due to differential neural processing within dorsal versus ventral cortical areas that represent lower versus upper visual fields, respectively. Here we test a novel hypothesis that this vertical asymmetry in global processing is a 3-D phenomenon associated with (1) higher ecological relevance of low-spatial frequency (SF) component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 73 publications
3
11
0
Order By: Relevance
“…Combining 7T imaging with MVPA, we demonstrate a role of dorsal areas (V3A, V7) in 3D perception, consistent with previous fMRI studies showing a) disparity-evoked fMRI responses in V1, V3A, and V7 ( Bridge and Parker, 2007 ; Preston et al, 2008 ; Goncalves et al, 2015 ; Rideaux and Welchman, 2019 ; Nasr and Tootell, 2020 ), b) discriminable multivoxel fMRI pattern responses to disparity-defined position (i.e., near vs. far planes) in V3A ( Preston et al, 2008 ; Goncalves et al, 2015 ; Patten and Welchman, 2015 ; Li et al, 2017 ; Liu et al, 2020 ). Our fMRI results extend beyond these previous studies by demonstrating layer-specific representations related to stereoscopic perception in V3A and V7 (i.e., higher MVPA accuracy for correlated than anti-correlated stimuli in upper than deeper layers).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Combining 7T imaging with MVPA, we demonstrate a role of dorsal areas (V3A, V7) in 3D perception, consistent with previous fMRI studies showing a) disparity-evoked fMRI responses in V1, V3A, and V7 ( Bridge and Parker, 2007 ; Preston et al, 2008 ; Goncalves et al, 2015 ; Rideaux and Welchman, 2019 ; Nasr and Tootell, 2020 ), b) discriminable multivoxel fMRI pattern responses to disparity-defined position (i.e., near vs. far planes) in V3A ( Preston et al, 2008 ; Goncalves et al, 2015 ; Patten and Welchman, 2015 ; Li et al, 2017 ; Liu et al, 2020 ). Our fMRI results extend beyond these previous studies by demonstrating layer-specific representations related to stereoscopic perception in V3A and V7 (i.e., higher MVPA accuracy for correlated than anti-correlated stimuli in upper than deeper layers).…”
Section: Discussionsupporting
confidence: 90%
“…Second, we demonstrate feedback connectivity specific to stereoscopic perception (i.e., stronger connectivity for correlated than anti-correlated stimuli) between deeper V1 and V3A layers, suggesting top-down influences to disparity processing in primary visual cortex through feedback from higher visual dorsal areas known to be involved in stereo vision and disparity ( Goncalves et al, 2015 ; Nasr and Tootell, 2020 ). Previous neurophysiology studies have shown attenuated responses in V1 for anti-correlated compared to correlated stimuli ( Cumming and Parker, 1997 ; also in circuit simulation: Samonds et al, 2013 ).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…However, this similarity in univariate activation patterns was less pronounced for the upper visual areas (lower visual field), rather an overall higher activation in upper V1 relative to lower V1 was observed regardless of visual trajectory. Asymmetry in the upper vs. lower visual quadrants has been previously reported and one possible explanation might be the distribution of ‘near-preferring’ neurons, which tend to be more frequent in lower VF compared to upper VF (Nasr & Tootell, 2018, 2020; Karim & Kojima, 2017). In general, psychophysiological studies demonstrated that lower visual field seems to be more thoroughly engaged in tasks from different domains, such as motion (Danckert & Goodale, 2001; Levine & McAnany, 2005, Lakha & Humphreys, 2005), colour discrimination and hue sensitivity (Levine & McAnany, 2005).…”
Section: Discussionmentioning
confidence: 78%
“…Relatively lower SF components are critical for extracting the Global shape in Navon figures, whereas higher SF components play a more significant role in the perception of local shapes (Flevaris & Robertson, 2016). The neural basis of this vertical asymmetry has been recently examined (Nasr & Tootell, 2020).…”
Section: Discussionmentioning
confidence: 99%